2012
DOI: 10.1111/j.1600-0625.2012.01520.x
|View full text |Cite
|
Sign up to set email alerts
|

Hailey–Hailey disease and tight junctions: Claudins 1 and 4 are regulated by ATP2C1 gene encoding Ca2+/Mn2+ATPase SPCA1 in cultured keratinocytes

Abstract: Mutations in the ATP2C1 gene encoding Ca2+/Mn2+ ATPase SPCA1 cause Hailey-Hailey disease (HHD, OMIM 16960). HHD is characterized by epidermal acantholysis. We attempted to model HHD using normal keratinocytes in which the SPCA1 mRNA was down-regulated with the small inhibitory RNA (siRNA) method. SiRNA inhibition significantly down-regulated the SPCA1 mRNA, as demonstrated by qPCR, and decreased the SPCA1 protein beyond detectable level, as shown by western analysis. The expression of selected desmosomal, adhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 28 publications
3
33
0
Order By: Relevance
“…In this case mutation in Ca 2+ /Mn 2+ -ATPases (SPCA1) located in the Golgi apparatus cause similar clinical and histological symptoms as those observed in Darier’s disease [60,71]. Additionally, translocation of DP and Dsg3 into desmosomes was reported to be delayed in SPCA1-deficient keratinocytes [72]. A more detailed mechanism explaining how defective function of SPCA1 affects desmosome assembly awaits further study.…”
Section: Disruption Of Desmosome Dynamics and Homeostasis In Human DImentioning
confidence: 77%
“…In this case mutation in Ca 2+ /Mn 2+ -ATPases (SPCA1) located in the Golgi apparatus cause similar clinical and histological symptoms as those observed in Darier’s disease [60,71]. Additionally, translocation of DP and Dsg3 into desmosomes was reported to be delayed in SPCA1-deficient keratinocytes [72]. A more detailed mechanism explaining how defective function of SPCA1 affects desmosome assembly awaits further study.…”
Section: Disruption Of Desmosome Dynamics and Homeostasis In Human DImentioning
confidence: 77%
“…Abnormal cytoplasmic Ca 2+ caused by haploinsufficiency of SPCA1 may alter post-translational modifications, including glycosylation, folding, trafficking and sorting, in cell adhesion molecules, leading to acantholytic changes seen in HHD (11)(12)(13). This study showed that different mutations in HHD result in distinct expression of mRNA and protein, which may relate to clinical phenotypes.…”
Section: Discussionmentioning
confidence: 93%
“…Desmoplakin null epidermis showed a similar increase in claudin-1 levels. While there have not been reports of tight junction activity in pemphigus patients, it is noteworthy that an upregulation of claudin 1 was found in Hailey-Hailey disease [32]. Hailey-Hailey disease results in blistering of the epidermis and is caused by a mutation in the ATP2C1 gene, resulting in desmosomal defects.…”
Section: Discussionmentioning
confidence: 98%